The Potential of Crypto Asset Insurance Protection in Indonesia - Ahwal Alienur Taufik (Syiah Kuala Law Journal, 2023)
In Indonesia the development of crypto assets is increasing, therefore this paper aims to accommodate legal instruments to provide a legal basis regarding the high potential for crypto asset insurance protection. In studying this, the author uses qualitative research methods with reasons that are more supportive in understanding the events, behavior, or phenomena of the emergence of this crypto asset. The author made this research to have an impact in creating legal instruments that will underlie crypto asset insurance protection in Indonesia. Because of the large potential digital assets that need to be protected from the start of the system, blockchain and other systems are vulnerable to being stolen, damaged or changed without the permission of the original owner. Referring to legal developments in China, Indonesia can see and study to participate in creating a similar legal basis to protect crypto assets. With the rapid development of technology in the world, it urges the government to form regulations regarding Crypto Assets. That way, there is potential for the creation of these legal instruments to protect crypto assets with insurance.